Superioritas Dalam Skena: Wacana Polisi Skena Dalam Musik Underground Studi Kasus Komunitas Youth Coffee Novotel Di Surakarta - Diajeng Stevani; Aris Setiawan (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2025)
This research aims to examine how the discourse of “scene police” influences the spread of superiority attitudes in the underground music community. In practice, the scene police emerge as a challenge that creates a symbolic surveillance mechanism that can reinforce attitudes of superiority among music lovers. The underground music scene in Surakarta has developed as an alternative space for self-expression and identity-seeking among Gen Z members. Through a qualitative approach with descriptive analytical methods, this research uses in-depth interviews, field observations and literature studies to analyze how the scene police are influential in the community. Alfred Adler's theory of personality focuses on how to overcome inadequacy by pushing one towards feelings of superiority. As such, the scene police become a form of judgment to meet the standards of their community. Rooted in a sense of inadequacy in gaining recognition, they make superiority an effort to create power. The results of the research from the underground music community of Youth Coffee Novotel show that knowledge of clothing styles, music tastes and the history of the formation of a music group is a benchmark for gaining identity recognition in the community. This results in an attitude of being the most informed and creates exclusivity to the point of social pressure, especially for new members. This suggests that many individuals in the underground music scene aim for recognition through exclusivity has become a significant motivation for superiority.